What Makes for a Successful Digital Health Integrated Program of Work? Lessons Learnt and Recommendations From the Melbourne Children's Campus - Hourani, Danah; Darling, Simone; Cameron, Eloise; Dromey, James; Crossley, Louise; Kanagalingam, Sanji; Muscara, Frank; Gwee, Amanda; Gell, Grace; Hiscock, Harriet; Anderson, Vicki (Frontiers in Digital Health, 2021)
Embedding digital technologies in healthcare has the potential to streamline and personalize medical care. However, healthcare systems are often fragmented, and therefore achieving a truly integrated digital health program can be challenging. To promote a streamlined, evidence-based approach to implementing digital health solutions in a healthcare system, the Murdoch Children's Research Institute (MCRI) established the Digital Health Translation and Implementation Program (DHTI) bringing together clinicians, researchers and digital health experts. From the program commencement, frontline clinical innovators have collaborated with DHTI team members to develop and implement digital solutions to address pain-points in the healthcare system. Throughout this program, important lessons have been learnt relating to the development, evaluation and implementation of digital solutions in the healthcare system. This paper explores these lessons and makes recommendations for the successful implementation of digital health solutions in healthcare systems under five main categories: (1) design and usability, (2) stakeholder engagement and uptake, (3) project management and resourcing, (4) process and implementation, and (5) evaluation. Recommendations suggested here are designed to support future healthcare-based digital health programs to maximize the impact digital solutions can have on the healthcare system and patients.